Implementation of the Science Process Skills Approach Accompanied by the Use of Static Fluid Modules in Fish Cage Buildings - Sri Septi Dyah Pratiwi; Trapsilo Prihandono; Lailatul Nuraini (Universitas Lambung Mangkurat, 2023)
This study aims to investigate the impact of the implementation of the science process skills approach in conjunction with a static fluid module of fish cage buildings on the physics and science process skills learning outcomes of high school students. Quantitative experiments are used in the research method. This study used interviews, observations, tests, documentation, and data collection methods. The SMA Negeri 5 Jember class XI MIPA was the location of the study, and there were two research groups: the experimental group and the control group. The indicators of science process skills used in this study are observing, concluding, communicating, making tables, analyzing experiments, and collecting and processing data. The finding demonstrated that learning with static fluid modules for fish cages in physics and the science process skills approach significantly impacted students' learning outcomes and science process skills. The T-test that was carried out revealed that sig. 2-tailed) is 0.000, it can be concluded that the static fluid module of fish cage buildings and the implementation of the science process skills approach significantly impact students' physics learning outcomes. The study concludes that a static fluid module for fish cages in physics learning in high school and the implementation of the science process skills approach significantly impact student learning outcomes and science process skills.